The use of project technologies in teaching the structure and maintenance of cars - V. Pryimak (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
The research focused on how the application of the project method in the educational process contributes to a deeper understanding of theoretical knowledge and the development of practical skills among students of technical specialities. In this study, an analysis of the effectiveness of design technologies in teaching the construction and maintenance of cars was carried out, which allowed assessing their impact on the development of theoretical and practical skills of students. It was found that the use of project technologies in teaching significantly improves the quality of students’ assimilation of theoretical knowledge and contributes to the development of practical skills. It was found that students who completed tasks in the form of projects better understood the principles of operation of automotive systems and were able to apply their knowledge in real situations. Practical work in the project format contributed to the development of critical thinking and the ability to make informed decisions, as participants were forced to analyse problems and find optimal ways to solve them. It was also found that the project method increased students' motivation to learn and encouraged them to independently search for information, collaborate in a team, and use modern diagnostic tools. Work in groups contributed to the development of communication and time management skills, which are important in professional activities. In general, the results of the study indicate a significant increase in the effectiveness of the educational process through the integration of the project method, which contributes not only to a deeper assimilation of theoretical knowledge, but also to the development of practical skills that directly affect the professional readiness of students of technical specialities. The results of this study can be used in educational institutions that train car maintenance specialists to improve training programmes and teaching methods